Mechanistic and functional integration of sirtuin deacylases: from substrate specificity to biological outcomes - Jian-long Zhang; Zi-Yu Dou; Yong-yue Fan; De-guan Sun; Xiong-jie Fan; Ze Yu; Guo-Cai Yang (Glycoconjugate Journal, 2026)

Coupled dynamic model of the vibratory roller-unsaturated subgrade and evolution of its dynamic response during vibratory compaction - An Liu; Zong-Tang Zhang; Bao-Jie Fan; Wei Hu; Kao-Xian Zhou; Ze Liu; Kai-Shun Liu (Soil Dynamics and Earthquake Engineering, 2026)

Discovery of garnet-bearing peraluminous ferroan granites in the Trans-North China Orogen: Evidence for anatexis of residual metasedimentary crust in a hot collisional orogen - Jing-Jing Fan; Caiyun Lan; Yong-Min Li; Jun Rao; Zi-Long Wang; Ze-Xian Cui; Meng-Jing Li; Xiaoping Long (Precambrian Research, 2026)

The unintentional adverse effect of Fe3 + on trimethoprim adsorption at environmentally relevant concentration by extracellular polymeric substances - You Ma; Tian-Yu Li; Zi-Yi Fan; Han Meng; Guo-Xiang Wang; Fang Fang; Yu-Dong Chen; Run-Ze Xu; Wen-Ming Xie (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Magnoflorine, a dietary alkaloid from Alpinia oxyphylla fruit, ameliorates colitis by restoring intestinal barrier and dual modulation of JAK/STAT3 pathway - Ze Ma; Xiang Li; Qin Tian; Hejing Shen; Fengzhong Wang; Yajuan Bai; Bei Fan (Food Chemistry, 2026)

Aquaculture-relevant florfenicol exposure causes hepatopancreatic bioaccumulation and metabolic-immune toxicity in the mud crab Scylla paramamosain - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Zhi-Long Chen; Xin-Jian Liu; Zhi-Xun Guo (Environmental Pollution, 2026)

Engineering a portable CRISPR/SPE-ECL platform for monkeypox pseudovirus aerosol detection - Xiaoyun Yin; Yang Liu; Bin Du; Zhiwei Liu; Jiwei Xu; Bing Liu; Ze Fan; Zhaoyang Tong (Chemical Engineering Journal, 2026)

Vegetation water status and topography shape drought-induced dieback of two Pinus species in Southwest China - Dao-Xiong Gao; Rao-Qiong Yang; Pei-Li Fu; De-Li Zhai; Ze-Xin Fan (Forest Ecology and Management, 2026)

Lignin depolymerization as a source of polycyclic aromatic hydrocarbons in agricultural waste composting - Fengting Qu; Yuran Yang; Mengxue Fan; Ze Deng; Hongyu Yang; Zimin Wei (Bioresource Technology, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

GNPS-guided discovery of antifungal brominated metabolites from Chaetomium elatum FH-3 via NaBr-regulation and biotransformation - Jing-jing Su; Yin-han Teng; Bai-xue Yin; Hai-fang Wang; Yu-ze Li; Wei Wang; Xiao-mei Song; Dong-dong Zhang; Hao Fan (Phytochemistry Letters, 2026)

A dual-stream LSTM–XGBoost framework for mine water inflow forecasting: a case study of the Longfeng coal mine - Wang Hao; Li Bo; Zeng Yi Fan; Liu Pu; Chen Wei; Wang Ze Hui; Che Lu Lu (Journal of Hydrology, 2026)

Green synthesis of a histidine-copper biomimetic enzyme for sustainable degradation of sulfamethoxazole in aquaculture wastewater - Yini Zhao; Long Cheng; Tao Yu; Long Gu; Xiangyi Zhang; Hangfei Gao; Zhicen Liu; Ze Fan; Ting Yan; Dongli Qin; Xinyue Zhao; Haijiao Xie; et al. (Journal of Environmental Chemical Engineering, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Dynamic responses of tension leg platforms considering the influence of tensioners based on a multi-stage feature extraction strategy - Jianwei Wang; Ze He; Minghua Yue; Lei Fan; Xinyu Han; Jiachen Chai; Xiaofan Jin (Ocean Engineering, 2026)

Antibody-drug conjugates in breast cancer brain and leptomeningeal metastases: mechanistic insights and therapeutic progress - Hanqi Zhang; Yaqing Qin; Hanzhi Chu; Yidan Fan; Jiayi Tang; Wei Deng; Xinhao Zheng; Ze Yuan; Yutian Zou; Yanan Kong (Cancer and Metastasis Reviews, 2026)

Contributions of recycled altered oceanic crust to sediment-dominated arc magma sources revealed by potassium isotopes - Zuxing Chen; Fang-Zhen Teng; Winnie X. Fan; Robert J. Stern; Ze-Zhou Wang; Yuxiang Zhang; Tian-Yi Huang; Xiaoyuan Wang; Zhigang Zeng (Geochimica et Cosmochimica Acta, 2026)

Hydrogen-bonding guided isoreticular supramolecular frameworks with self-recovery for efficient natural gas purification - Zhou-Rui Yan; Xiao-Han Li; Shi-Kai Zheng; Ze-Jiu Diao; Fan Li; Jin-Peng Liu; Guoliang Liu; Lin-Bing Sun (Chemical Engineering Journal, 2026)

The integration of transcriptomics, intestinal microbiota and physiology reveals the toxic mechanism of cephalexin in rainbow trout - Chenyang Zhao; Peng Fan; Tianqing Huang; Zhicen Liu; Hangfei Gao; Wei Gu; Junwei Wang; Xinyang Wang; Ze Fan; Lei Gao; Gefeng Xu (Aquatic Toxicology, 2026)

Excavation Damage Evaluation of Rock Anchor Beam Based on Acoustic P-Wave Velocity and RFD Index in Highly Stressed Powerhouse: A Case Study of Baihetan Hydropower Station, China - Jin-Shuai Zhao; Lei Xia; Yong Fan; Quan Jiang; Bing-Rui Chen; Guang-Dong Yang; Dong-Ze Wang (Rock Mechanics and Rock Engineering, 2026)

Pain-Affective Disorder Comorbidity in the Temporomandibular Disorders: From Mechanistic Insights to Clinical Management - Zhaoyichun Zhang; Shibin Yu; Shengxi Wu; Zuolin Jin; Ze Fan; Jing Huang (Neuroscience Bulletin, 2026)

Physiological and transcriptomic insights into the stress response of mud crab Scylla paramamosain (Estampador, 1950) to low salinity - Chang-Hong Cheng; Min-Ze Liao; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Marine Environmental Research, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Study on the influence mechanism of bionic undulating fin parameters on hydrodynamic performance and flow field characteristics - Ze-jun Liang; Peng Xu; Yi-wei Fan; Dong-yang Chen; Kun-de Yang (Ocean Engineering, 2026)

Per-and poly-fluoroalkyl substances in lung tissues and their association with lung cancer - Xi-Ze Min; Li Ma; Fei Chen; Ying-Hua Hu; Chao Jiang; Yi-Fan Li; Yue Han; Zi-Feng Zhang; Kurunthachalam Kannan (Journal of Hazardous Materials, 2026)

Robust multifunctional rGO/ZIF-8@PPS fibrous membrane for effective oil-water separation in harsh environments - Yang Liu; Tingting Fan; Changhao Liu; Yun-Ze Long (Journal of Environmental Chemical Engineering, 2026)

Effects of mechanized harvesting on sesame seed storage: Quality, volatile compounds, and metabolites - Yun-Long Chang; Yu-Long Niu; Jia-Rui Li; Zi-Fan Zhang; Hua-Min Liu; Xue-De Wang; Xin-Yu Wen; Hong-Yu Zhang; Hong-Wei Liu; Shao-Ze Zhang (Food Chemistry, 2026)

Day-night asymmetry in lower band chorus waves - Yun Yan; Chao Yue; Li Li; Qianli Ma; Yoshiharu Omura; Shan Wang; Qiu-Gang Zong; Xu-Zhi Zhou; Ze-Fan Yin; Yi-Xin Hao; Jing-Huan Li; Zi-Kang Xie (Science China Earth Sciences, 2026)

Study on GPR Forward Modeling and Intelligent Identification of Subgrade Defects Characterized by Hidden Voids - Bin Wu; Yan-li Qi; Qi-guang Cheng; Fan-meng Kong; Yu-xuan Han; Yiguo Xue; Yue-hua Wu; Sheng-yong Dong; Ze-zhou Kang; Zhe Zhang; Yong-feng Shi; Min Han (Applied Geophysics, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Host-associated volatile cues drive foraging behavior of Trichopria drosophilae toward Drosophila suzukii-infested fruits - Hai-Kuan Sun; Fan Yang; Ze-Hua Wang; Ren Li; Guang-Hang Qiao; Qiu-Fei Li; Yu-Yu Wang; Shan-Ning Wang (Journal of Pest Science, 2026)

Organic chemicals of Arctic concern in Russian coastal seas - Xi-Ze Min; Xianming Zhang; Zhi-Yong Xie; Anatoly Nikolaev; Katrin Vorkamp; Jian-Min Ma; Lars-Otto Reiersen; Li Li; Ming-Hong Cai; Nan-Qi Ren; Yi-Fan Li; Zi-Feng Zhang; et al. (Science Bulletin, 2026)

Research on the impact of resident behavior on energy consumption during the heating period of ultra-low energy buildings - Ru-Xi Ding; Jia-Ze Dai; Ying-Nan Zhang; Xiao-Ping Wu; Cong-Han Yu; Zhenfa Fan (Energy and Buildings, 2026)

Closed-loop recycling and recovery of vanadium cathodes from waste aqueous zinc-ion batteries - Hsing-Kai Tseng; Jun-An Su; I-Mao Chen; Yu-Ze Chen; Jun-Yi Wu; Pin-Han Chen; Fan-Wei Liu (Chemical Engineering Journal, 2026)

Mud crab reovirus infection disrupts the intestinal microbiota and intestinal physiological homeostasis in mud crabs (Scylla paramamosain) - Min-Ze Liao; Chang-Hong Cheng; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Sheng-Kang Li; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2026)

Caspase-3 plays a pivotal role in Acinetobacter johnsonii-induced pyroptosis of black rockfish (Sebastes schlegelii) lymphocytes - Xuangang Wang; Fan Zhang; Qiannan Chen; Zhixiang Duan; Hengshun Li; Ze Tao; Xiangfu Kong; Quanqi Zhang; Haiyang Yu (Aquaculture, 2026)

Boron-phosphorus dual-doped graphene supported AuPd nanocatalyst for high-efficiency direct methanol and formic acid fuel cells: Toward sustainable energy solutions - Ze Qin; Henan Shang; Qiuyue Fan; Qi Jia; Lubin Sun; Sijia Li (Fuel, 2026)

Insights into the oxidation regime of diesel soot during realistic DPF regeneration - Zheng Fu; Chenyang Fan; Ye Liu; Ze Guan; Mingliang Wei; Bin Xu; Tansu Shang; Weiwei Shang (Fuel, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Soil moisture dynamics and rainfall infiltration across vegetation types in subtropical ecosystems in Southwest China - Qiao-Shun Yan; Yu-Xi Peng; Xiao-Jin Jiang; Pei-Li Fu; Zhi-Yun Lu; Xiao-Wen Hu; Yong-Jiang Zhang; Jiao-Lin Zhang; Ze-Xin Fan (CATENA, 2026)

Diversity and seasonal dynamics of parasitoid communities sustaining biocontrol of citrus leafminer moth Phyllocnistis citrella - Xin-Yi Chen; Yu-Tong Zhou; Pei-Ping Xu; Ze-Yun Fan; Li-He Zhang; Guillaume Nyagatare; Bao-Li Qiu (Biodiversity and Conservation, 2026)

Ophiocordyceps polystromata , a new entomopathogenic fungus from the Gaoligong Mountains in western Yunnan, China - He-Fa Liao; Ping-Ping Su; Ze-Mei Chen; Luo-Dong Huang; Qi Fan; Qiu-Lu Yang; Zhu-Liang Yang; Wei-Hong Hu; Yuan-Bing Wang (New Zealand Journal of Botany, 2025)

Recycled oceanic crust restricting trace element enrichment in mid-ocean ridge basalts - Fan Yang; Xiao-Long Huang; Yi-Gang Xu; Yang Yu; Peng-Li He; Le Zhang; Ze-Xian Cui (Lithos, 2025)

Micron-sized iron-sulfur minerals orchestrate micro-interface redox processes for sustainable wastewater treatment - Xin-Han Chen; Ze-Fan Chen; Chen-Peng Fang; Zhi-Zeng Zhao; Xiao-Qiang Cao; Jian Zhang; Zhao-Jing Zhu; Gang Zhou; Yi-Fan Wang; Lu-Cheng Fan; Li-Jiang Wu (Journal of Water Process Engineering, 2025)

Climatic influences on annual and intra-annual xylem anatomical traits of four coniferous tree species in the central Hengduan Mountains, Southwest China - Ju-Mei Zhang; Zaw Zaw; Pei-Li Fu; Shankar Panthi; Jambay Dema; Tong-Liang Xu; Hui Zhang; Achim Bräuning; Ze-Xin Fan (Dendrochronologia, 2025)

CDK5-Induced HCN2 Channel Dysfunction in the Prelimbic Cortex Drives Allodynia and Anxiety-Like Behaviors in Neuropathic Pain - Lu Chen; Shuai Cao; Yun-Ze Liu; Qi-Fan Yang; Jin-Yu Yang; Dan-Yang Zhang; Guo-Guang Xie; Xiang-Sha Yin; Ying Zhang; Yun Wang (Neuroscience Bulletin, 2025)

Progress in the application of DIC technology to rock mechanics testing: a review - Hao-fan Luo; Yang Tang; Wen-tao Feng; Jian-feng Liu; Hua Li; En-ze Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Development and characterization of magnetic cellulose adsorbents functionalized with polyacrylic acid - Chengmin Hou; Zi'’ang Zhao; Fanglin Li; Yuan Bai; Chuangchuang Ren; Chenyu Li; Ze Fan; Wanting Jia; Ying Zhang; Weimin Yan; Yuru Li; Yiting Yang; et al. (Journal of Water Process Engineering, 2025)

Cinnabar-dependent eye pigmentation mediates light input for circadian behavior synchronization in Spodoptera frugiperda - Zi-Jing Zheng; Shen-Lei Li; Shu-Ting Fan; Ze-Yuan Zhang; Shang-Huan Huang; Xi-Yu Ye; Guan-Heng Zhu (Journal of Insect Physiology, 2025)

Chlorite and associated influence on reservoir properties in tight sandstones of the Upper Shaximiao Formation, SW Sichuan Basin, China - Yunbiao Zhao; Fan Huang; Zhenghui Chen; Zhi Zhao; Hong Yu; Ze Liu; Chenhui Zhao (Journal of Asian Earth Sciences, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Micro-finned nanostructured superhydrophobic surfaces for high-performance steam condensation heat transfer at high concentrations of non-condensable gases - Wen-Ze Yang; Tian-Yu Zhang; Zhen-Yu Lu; Xuan-Yi Lin; Li-Wu Fan (Chemical Engineering Journal, 2025)

Assessment on Chlorella (Chlorella sorokiniana) meal as a substitution for fishmeal in Songpu mirror carp (Cyprinus carpio Songpu) feed: Effect on growth, intestinal health and microflora composition - Ze Fan; Yiqi Gao; Siwei Xiong; Chenhui Li; Di Wu; Jinnan Li; Liansheng Wang (Aquaculture, 2025)

Susceptibility of mud crabs (Scylla paramamosain) to the infection with decapod iridescent virus 1 - Min-Ze Liao; Hong-Ling Ma; Chang-Hong Cheng; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Juan Feng; Xin-Jian Liu; Zhi-Long Chen; Zhi-Xun Guo (Aquaculture, 2025)

The climate-driven mechanisms of sedimentary evolution in the mud area southwest off Cheju Island during the Holocene - Jingyi Cong; Huisong Fan; Shipu Bi; Xi Mei; Yanguang Dou; Zhonglei Wang; Ze Ning; Yong Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Green spaces and preventable disease and economic burdens in China from 2000 to 2020: A health impact assessment study - Hui-Ling Qiu; Hui-Yun Chen; Yu-Ting Xie; Gang-Long Zhou; Kai-Ze Yang; Hai-Juan Huang; Jian-Cheng Jiang; Xiao-Qi Zhu; Lu Wang; Kexin Yan; Guang-Hui Dong; Shujun Fan; et al. (Landscape and Urban Planning, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Prediction of multi-task physicochemical indices based on hyperspectral imaging and analysis of the relationship between physicochemical composition and sensory quality of tea - Xinna Jiang; Xingda Cao; Quancheng Liu; Fan Wang; Shuxiang Fan; Lei Yan; Yuqing Wei; Yun Chen; Guijun Yang; Bo Xu; Quan Wu; Ze Xu; et al. (Food Research International, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Inhibition of KDM6B prevents osteoarthritis by blocking growth plate-like H3K27me3 loss in bivalent genes - Hao Du; Yao Zhang; Xi Yu; Xuanhe You; Diwei Wu; Ze Du; Yongrui Cai; Zhenyu Luo; Hanpeng Lu; Zhixin Liao; Bi-Sen Ding; Ya Zhao; et al. (Science China Life Sciences, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Associations among Angiotensin-Converting Enzyme, Neuroinflammation, and Cerebrospinal Fluid Biomarkers of Alzheimer's Disease in Non-Dementia Adults - Lan-Yang Wang; Hao Hu; Ze-Hu Sheng; He-Ying Hu; Ya-Nan Ou; Fan Guo; Yang-Ke Zhu; Lan Tan (Neurotoxicity Research, 2025)

Nitrogenous chemical constituents and their antitumor activities evaluation in vitro from the aerial parts of Corydalis impatiens (pall.) Fisch - Ze-dong Nan; Yi-dong Zhu; Chao-fan Deng; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Natural Product Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Multi-model and naked-hand wearable sensing system based on direct writing Ag-TPU composite with porous microstructure for human–computer interactions - Yun-Fan Wang; Xiao-Yang Zhang; Jun-Yang Liu; Yuan-Jun Song; Yu-Qing Ni; Ze-Xian Chen; Yuan-Chun Li; Tong Zhang (Chemical Engineering Journal, 2025)

Application of machine learning to predict the fluoride removal capability of MgO - Lin Fan; Dexi Wang; Honglei Yu; Ze Gong; Yan He; Jinyuan Guo (Journal of Environmental Chemical Engineering, 2025)

Effects of Encarsia formosa (Hymenoptera: Aphelinidae) parasitism on the feeding preference and performance of the whitefly predator Serangium japonicum (Coleoptera: Coccinellidae) - Yi-Han Li; Ze-Yun Fan; Zhan-Peng Zhu; Xiao-Lu Lv; Muhammad Musa Khan; Jing-Chen Sun; Bao-Li Qiu (Crop Protection, 2025)

Discovery of cycloheptapeptides phakefusins A−E from the marine sponge Phakellia fusca based on molecular networking - Ying Wu; Zhao-Ze Xu; Can Kong; Shuai-Shuai Zhang; Xin-Li Lin; Si Zhang; Li-Yun Liu; Fan Sun; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Tissue distribution and residue depletion of difloxacin in crucian carp (Carassius carassius) after multiple oral administration - Fan Yang; Kai-Li Ma; Yue Liu; Yang-Guang Jin; Yan-Ni Zhang; Yan Dai; Ming-Hui Duan; Ze-En Li; Fang Yang (Aquaculture, 2024)

Detecting the extreme hydrological events over China in 2022 using sparse GNSS and GRACE/GRACE-FO - Ze Wang; Weiping Jiang; Jian Wang; Dongzhen Wang; Wenlan Fan; Meilin He (Remote Sensing of Environment, 2024)

Reconstruction of hydroclimate variability in southern Laos from 1885 to 2019 based on Pinus latteri tree-ring data - Nakhonekham Xaybouangeun; Zaw Zaw; Rao-Qiong Yang; Shankar Panthi; Dao-Xiong Gao; Viengsy Paothor; Ze-Xin Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

High-affinity potassium transporter TaHAK1 implicates in cesium tolerance and phytoremediation - Jin Liu; Shuai-Bo Chen; Ze-Hua Fan; Haitao Liu; Yinglong Chen; Chandra Shekhar Seth; Evgenios Agathokleous; Tian-Cai Guo; Guo-Zhang Kang; Ge-Zi Li (Journal of Hazardous Materials, 2024)

Efficient removal of radioactive Th(IV) and U(VI) from rare earth leaching solution using HDES - Lei-Tao Sha; Qiang Wu; Yi-Fan Zhang; Wei-Jia Wang; Fei Wu; Qing-Gang Huang; Ze-Yi Yan (Chemical Engineering Journal, 2024)

Microglial EPOR Contribute to Sevoflurane-induced Developmental Fine Motor Deficits Through Synaptic Pruning in Mice - Danyi He; Xiaotong Shi; Lirong Liang; Youyi Zhao; Sanxing Ma; Shuhui Cao; Bing Liu; Zhenzhen Gao; Xiao Zhang; Ze Fan; Fang Kuang; Hui Zhang (Neuroscience Bulletin, 2024)
Clinical researches including the Mayo Anesthesia Safety in Kids (MASK) study have found that children undergoing multiple anesthesia may have a higher risk of fine motor control difficulties. However, the underlying mechanisms remain elusive. Here, we report that erythropoietin receptor (EPOR), a microglial receptor associated with phagocytic activity, was significantly downregulated in the medial prefrontal cortex of young mice after multiple sevoflurane anesthesia exposure. Importantly, we found that the inhibited erythropoietin (EPO)/EPOR signaling axis led to microglial polarization, excessive excitatory synaptic pruning, and abnormal fine motor control skills in mice with multiple anesthesia exposure, and those above-mentioned situations were fully reversed by supplementing EPO-derived peptide ARA290 by intraperitoneal injection. Together, the microglial EPOR was identified as a key mediator regulating early synaptic development in this study, which impacted sevoflurane-induced fine motor dysfunction. Moreover, ARA290 might serve as a new treatment against neurotoxicity induced by general anesthesia in clinical practice by targeting the EPO/EPOR signaling pathway.

Molecular characterization, expression and immune functional analysis of cystatin 10 in turbot - Fan Zhang; Zhixiang Duan; Qiannan Chen; Xuangang Wang; Hengshun Li; Ze Tao; Zhentao Chen; Gan Yu; Haiyang Yu (Molecular Biology Reports, 2024)

Integrated scRNAseq analyses of mouse cochlear supporting cells reveal the involvement of Ezh2 in hair cell regeneration - Yifan Zhao; Ze Xu; Ran Zhang; Mingli Liu; Chengcheng Lu; Chunxin Fan; Jian Wang (Molecular Biology Reports, 2024)

Role of ASC, a key component of the inflammasome in the antimicrobial process in black rockfish (Sebastes schlegelii) - Ze Tao; Xuangang Wang; Hengshun Li; Dianyang Zhou; Qiannan Chen; Zhixiang Duan; Fan Zhang; Zhentao Chen; Gan Yu; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Astronomical forcing of terrestrial organic carbon burial in East Asia during the Eocene - Juan Liu; Juye Shi; Yongchao Lu; Xiaojie Fan; Ze Zhang; Rui Zhang; Zhixiang Wang; Ke Xu; Anguo Xiao; David B. Kemp; Chunju Huang (Earth and Planetary Science Letters, 2024)

Nanofiber aerogel with layered array with structure coupled photothermal/magnetothermal effect for continuous seawater desalination - Zichen Yu; Tingting Fan; Yang Liu; Bowen Yang; Luyao Wang; Fang Yin; Yuan Gao; Yun-Ze Long (Chemical Engineering Journal, 2024)

Heteroelectrocatalyst MoS2@CoS2 modified separator for Li-S battery: Unveiling superior polysulfides conversion and reaction kinetics - Chuanbao Tu; Ze Zhang; Xingtao Qi; Fan Wang; Zhenyu Yang (Chemical Engineering Journal, 2024)

Deciphering the pivotal material properties of perovskite for hydrogen production in tar catalytic cracking - Wang-mi Chen; Bei-dou Xi; Mei-ying Ye; Ming-xiao Li; Jia-qi Hou; Yu-fang Wei; Cheng-ze Yu; Fan-hua Meng (Fuel, 2024)

Evaluation of four novel non-grain protein sources completely replacing soybean meal on growth performance, serum biochemistry, amino acid transport and intestinal health of grass carp (Ctenopharyngodon idella) at different water temperatures - Di Wu; Ze Fan; Xianhu Zheng; Jinnan Li; Meng Zhou; Haitao Zhang; Hong Xu; Shouqi Xie; Liansheng Wang (Fish & Shellfish Immunology, 2024)

Influence of Different Stages of Post-Traumatic Elbow Joint Capsule Healing on Pronation Movement - Fang Wang; Xin-Jie Chang; Ming-Xin Li; Ming-Ze Zhou; Bo-Tian Tian; Jian-Guo Zhang; Yu-Bo Fan (Journal of Medical and Biological Engineering, 2024)

Genome-wide identification, characterization, molecular evolution and expression profiling analysis of scavenger receptors in black rockfish (Sebastes schlegelii) - Zhentao Chen; Xuangang Wang; Gan Yu; Jingrun Pu; Xuechen Li; Ze Tao; Zhixiang Duan; Fan Zhang; Ping Han; Hengshun Li; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

C-type lectin 12B/4E of black rockfish (Sebastes schlegelii) macrophages as pattern recognition receptors in the antibacterial mechanism of exploration - Zhixiang Duan; Fan Zhang; Xuangang Wang; Hengshun Li; Dianyang Zhou; Qiannan Chen; Ze Tao; Zhentao Chen; Gan Yu; Haiyang Yu (Fish & Shellfish Immunology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

“Image-Spectral” fusion monitoring of small cotton samples nitrogen content based on improved deep forest - Shizhe Qin; Yiren Ding; Tailong Zhou; Mingcan Zhai; Zhenghang Zhang; Mengxin Fan; Xin Lv; Ze Zhang; Lifu Zhang (Computers and Electronics in Agriculture, 2024)

Two new cytotoxic diterpenoid alkaloids from Delphinium grandiflorum - Ze-dong Nan; Ying Shang; Chao-fan Deng; Yi-dong Zhu; Guo-dong Jiang; Zhen-zhen Wang; Chong-long Li; Xiao-li Ma; Zhi-Bo Jiang (Phytochemistry Letters, 2024)

Growth-climate relationships of four tree species in the subtropical evergreen broad-leaved forests in Southwest China - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Pei-Li Fu; Shankar Panthi; Achim Bräuning; Ze-Xin Fan (Dendrochronologia, 2024)

Fer-1 Protects against Isoflurane-Induced Ferroptosis in Astrocytes and Cognitive Impairment in Neonatal Mice - Peng Zhang; Xiaotong Shi; Danyi He; Yu Hu; Yongchao Zhang; Youyi Zhao; Sanxing Ma; Shuhui Cao; Meiting Zhai; Ze Fan (Neurotoxicity Research, 2024)

The impact of elevated CO2 concentration on photosynthesis, growth and hydraulics of evergreen and deciduous tree seedlings from a subtropical forest in Southwest China - Pei-Li Fu; Ya Zhang; Jin-Hua Qi; Yong-Jiang Zhang; Guang-You Hao; Patrick M. Finnegan; Qiao-Shun Yan; Ze-Xin Fan (Agricultural and Forest Meteorology, 2024)

Revelation of benzo(a)pyrene-induced latent toxicity mechanism to intestinal histomorphology and oxidative status for common carp (Cyprinus carpio) through transcriptional and single-cell sequencing - Qirui Hao; Zhongxiang Chen; Ze Fan; Song Wu; Shuyan Bai; Ningning Du; Chenhui Li; Peng Wang; Rongwei Zhao; Li Huang; Lei Gao (Aquaculture, 2024)

Occurrence and fate of pharmaceuticals and personal care products in a wastewater treatment plant with Bacillus bio-reactor treatment - Xi-Ze Min; Zi-Feng Zhang; Xi-Mei Lu; Jia-Cheng Chen; Wan-Li Ma; Li-Yan Liu; Wen-Long Li; Yi-Fan Li; Roland Kallenborn (Science of The Total Environment, 2024)

Asiaticasics A-O, structurally intriguing coumarins from Toddalia asiatica with potential inflammatory inhibitory activity - Si-Chen Song; Bai-Dong Ren; Xue-Wen Wu; Yi-Fan Xie; Bin Cheng; Qiong Wei; Wen-Hui Pang; Ze-Kai Wu; Xing-Jie Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2024)

Nitazoxanide protects against experimental ulcerative colitis through improving intestinal barrier and inhibiting inflammation - Hu-Tai-Long Zhu; Jing Luo; Yi Peng; Xiao-Fan Cheng; Shang-Ze Wu; Yin-Di Zhao; Le Chang; Zhi-Jie Sun; De-Li Dong (Chemico-Biological Interactions, 2024)

Preparation of geopolymer based on municipal solid waste incineration fly ash-phosphorus slag and its function for solidification of heavy metals - An Sai; Wang Baomin; Chen Wenxiu; Yu Ze; Fan Chengcheng (Waste Management, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

Seasonal patterns, fate and ecological risk assessment of pharmaceutical compounds in a wastewater treatment plant with Bacillus bio-reactor treatment - Zi-Feng Zhang; Ying-Ying Fan; Xi-Mei Lu; Xi-ze Min; Wan-Li Ma; Li-Yan Liu; Yi-Fan Li; Wen-Long Li (Journal of Environmental Management, 2024)

Direct characterization of deep soil water depletion reveals hydraulic adjustment of apple trees to edaphic changes - Xia Wang; Yanli Fan; Meifang Yan; Ze Tao; Dong He; Guangyuan Du; Huijie Li; Esteban Jobbagy; Min Li; Bingcheng Si (Agricultural and Forest Meteorology, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Distribution and accumulation of Cadmium in different trophic levels affecting Serangium japonicum, the predatory beetle of whitefly Bemisia tabaci, biologically, physiologically and genetically: An experimental study - Muhammad Musa Khan; Ze-Yun Fan; Xing-Min Wang; Bao-Li Qiu (Journal of Hazardous Materials, 2024)

Spatial distribution, source identification, and transportation paths of plutonium in the Beibu Gulf, South China Sea - Yong-jing Guan; Hua He; Kai-di Fan; Shen-zhen Wang; Zi-chen Guo; Hui-juan Wang; Liang-jia Cui; Wu Chen; Chun-ping Huang; Zhi-yong Liu; Xian-wen He; Kai-xing Guo; et al. (Marine Pollution Bulletin, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Analysis of Edwardsiella piscicida induced transcriptome profiles in macrophages of black rockfish (Sebastes schlegelii) provides insights into the trigger of pyroptosis - Xuangang Wang; Xiangfu Kong; Hengshun Li; Ying Chen; Ze Tao; Fan Zhang; Zhixiang Duan; Zhentao Chen; Jinxiang Liu; Quanqi Zhang; Haiyang Yu (Aquaculture, 2023)

Nightmare or delight: Taxonomic circumscription meets reticulate evolution in the phylogenomic era - Ze-Tao Jin; Richard G.J. Hodel; Dai-Kun Ma; Hui Wang; Guang-Ning Liu; Chen Ren; Bin-Jie Ge; Qiang Fan; Shui-Hu Jin; Chao Xu; Jun Wu; Bin-Bin Liu (Molecular Phylogenetics and Evolution, 2023)

Analysis of spatial structure and filling mechanism of a paleokarst channel against a background of denudation: A case study in the Tahe Oilfield, Tarim basin - Chenhe Zhang; Zhiqian Gao; Tailiang Fan; Debin Yang; Duan Wei; Jun Wu; Jinxian Liu; Huitao Zhang; Xinlei Zhang; Bo Li; Zhe Chang; Yu Gu; et al. (Marine and Petroleum Geology, 2023)

Himalaya to Hengduan: dynamics of alpine treelines under climate change - Achyut Tiwari; Arjun Adhikari; Ze-Xin Fan; Shu-Feng Li; Alistair S. Jump; Zhe-Kun Zhou (Regional Environmental Change, 2023)

Mechanism of the toxic effects of tetracycline on blood meal digestion in Haemaphysalis longicornis - Yan-Kai Zhang; Si-Si Li; Chen Yang; Yu-Fan Zhang; Jing-Ze Liu (Experimental and Applied Acarology, 2023)

The evolution of insecticide resistance in the white backed planthopper Sogatella furcifera (Horvath) of China in the period 2014–2022 - Ya-Ting Liu; Xin-Yu Song; Bin Zeng; Wen-Jing Zhang; Xing-Yu Chen; Ze-Rui Feng; Hua-Yang Yu; Cong-Fen Gao; Shun-Fan Wu (Crop Protection, 2023)

Microplastics affect soil bacterial community assembly more by their shapes rather than the concentrations - Peng-Yang Wang; Ze-Ying Zhao; Xiao-Bin Xiong; Ning Wang; Rui Zhou; Zhi-Ming Zhang; Fan Ding; Meng Hao; Song Wang; Yue Ma; Aimee Grace Uzamurera; Kai-Wen Xiao; et al. (Water Research, 2023)

Tree rings in Tsuga dumosa reveal increasing drought variability in subtropical southwest China over the past two centuries - Yun-Li Yin; Zaw Zaw; Xin-Hua Peng; Hui Zhang; Pei-Li Fu; Wen-Li Wang; Achim Bräuning; Ze-Xin Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A novel method for solidification/stabilization of MSWI fly ash by graphene nanoplatelets synergistic alkali-activated technology - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Journal of Environmental Chemical Engineering, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Comparative Pollution Toxicity and Chemical Speciation of Heavy Metals in MSWI Fly Ash with Different Particle Size Distribution - Chengcheng Fan; Baomin Wang; Yi Xu; Hainan Ma; Ze Liu (Water, Air, & Soil Pollution, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Current and potential trends in the bioactive properties and health benefits of Prunus mume Sieb. Et Zucc: a comprehensive review for value maximization - Tiantian Tian; Hui Cao; Mohamed A. Farag; Siting Fan; Luxuan Liu; Wenjing Yang; Yuxuan Wang; Liang Zou; Ka-Wing Cheng; Mingfu Wang; Xiaolei Ze; Jesus Simal-Gandara; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Effects of dietary α-ketoglutarate on the growth performance, digestive enzymes, tor signaling pathway and intestinal microbiota of juvenile mirror carp (Cyprinus carpio) fed low phosphorus diets - Liansheng Wang; Ze Fan; Di Wu; Jinnan Li; Qiyou Xu; Linghong Miao; Xianping Ge; Dingcheng Cao; Xianhu Zheng (Aquaculture, 2023)

Momordica charantia saponins administration in low-protein-high-carbohydrate diet improves growth, blood biochemical, intestinal health and microflora composition of juvenile common carp (Cyprinus carpio) - Ze Fan; Liansheng Wang; Jinnan Li; Di Wu; Chenhui Li; Xianhu Zheng; Haitao Zhang; Linghong Miao; Xianping Ge (Fish & Shellfish Immunology, 2023)

Effect of nano silica on solidification/stabilization of heavy metal in alkali-activated MSWI fly ash solidified body - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Process Safety and Environmental Protection, 2023)

The impact of warming climate on Himalayan silver fir growth along an elevation gradient in the Mt. Everest region - Narayan Prasad Gaire; Zaw Zaw; Achim Bräuning; Jussi Grießinger; Bimal Sharma; Prabina Rana; Sanjaya Bhandari; Saroj Basnet; Ze-Xin Fan (Agricultural and Forest Meteorology, 2023)

Fine-tuning immunity against cancer: the emergence of engineered commensal microbiota - Shi-Jun He; Fan Yang; Jian-Ping Zuo; Ze-Min Lin (Science Bulletin, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Shock-induced potassium and zinc isotope fractionation in ordinary chondrites and its implications - Ying-Kui Xu; Zhi Li; Shi-Jie Li; Ze-Zhou Wang; De-Liang Wang; Yan Fan; Xiong-Yao Li; Jian-Zhong Liu; Dan Zhu (Geochimica et Cosmochimica Acta, 2023)

Diesel soot combustion over ceria catalyst: Evolution of functional groups on soot surfaces - Jiangjun Wei; Chenyang Fan; Yuan Zhuang; Zheng Fu; Ze Guan; Haizhao Li; Deliang Li; Yejian Qian (Fuel, 2023)

Association of occupational exposure to polycyclic aromatic hydrocarbons in workers with hypertension from a northeastern Chinese petrochemical industrial area - Yu Sun; Ze Kan; Zi-Feng Zhang; Li Song; Chao Jiang; Ji Wang; Wan-Li Ma; Yi-Fan Li; Li Wang; Li-Yan Liu (Environmental Pollution, 2023)

Spatial minimum temperature reconstruction over the last three centuries for eastern Nepal Himalaya based on tree rings of Larix griffithiana - Narayan P. Gaire; Santosh K. Shah; Bimal Sharma; Nivedita Mehrotra; Uday Kunwar Thapa; Ze-Xin Fan; Prakash Chandra Aryal; Dinesh Raj Bhuju (Theoretical and Applied Climatology, 2023)

Superhydrophobic aerogel blanket with magnetic and solar heating effect enables efficient continuous cleanup of highly viscous crude oil - Xueyan Wang; Xianfeng Liu; Zhong Liu; Wenying Cui; Shilong Gao; Jun Zhang; Tingting Fan; Seeram Ramakrishna; Yun-Ze Long (Journal of Hazardous Materials, 2023)

Shrub encroachment increases soil erosion risk in hillside alpine meadows of the Qinghai-Tibetan Plateau, NW China - Yi-Fan Liu; Hui Fang; Ze Huang; Pedro A.M. Leite; Yu Liu; Manuel López-Vicente; Jingxue Zhao; Zhi-Hua Shi; Gao-Lin Wu (CATENA, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Effects of ocean states coupling on the simulated Super Typhoon Megi (2010) in the South China Sea - Minglin Zheng; Ze Zhang; Weimin Zhang; Maoting Fan; Huizan Wang (Frontiers in Marine Science, 2023)
Responses of the South China Sea (SCS) to a typhoon are complex due to the susceptible upper layer and active multiscale motions and thus need to be urgently resolved and validated in numerical simulations. A coupled atmosphere–ocean–wave model and various in-situ observations were applied to understand the strong interactions between Super Typhoon Megi (2010) and the SCS, especially the wave effects on typhoon simulation. Five sensitive experiments using different combinations of models were firstly conducted and compared to validate the effectiveness of the ocean coupling. Compared with WRF-only and ROMS-only outputs, the coupled experiments evidently improved the accuracy of typhoon intensity, the typhoon-induced cold wake, and significant wave height, along with the thermodynamical responses in the upper 400 m layer, including the near-inertial currents, the variation in ocean heat content, and mixed layer depth. However, the differences between WRF-ROMS and COAWST were slight, though the significant wave height was more than 9 m high in COAWST. Further analysis showed that the modification of heat flux, which could cancel out the effect due to the wave-induced surface roughness, is consistent with that of momentum flux in the wave-coupled experiment. This resulted in similar overall results. To further figure out the wave effects on typhoon and eliminate the contingency brought by the surface physical parameterization scheme, six experiments using three surface physical parameterization schemes were designed with and without wave coupling, separately. The sensible heat flux showed significant differences between three schemes, followed by the latent heat flux and the correspondingly changing momentum loss. Results support the above-mentioned conclusion that the typhoon intensity was determined by the net surface flux. Our findings highlight the necessity in using a high-resolution coupled atmosphere–ocean–wave model and proper surface physical parameterization, especially when coupling waves to make accurate regional numerical environment predictions.

Unsupervised classification of polarimetric SAR images via SV G p 0 MM with extended variational inference - Ze-Chen Li; Heng-Chao Li; Gui Gao; Ze-Xi Hua; Fan Zhang; Wen Hong (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

A facile method to achieve red thermally activated delayed fluorescence emitters with EQE over 30% via molecular aspect ratio engineering - Jing-Xing Liang; Ze-Hui Pan; Kai Zhang; Dezhi Yang; Jing-Wen Tai; Chuan-Kui Wang; Man-Keung Fung; Dongge Ma; Jian Fan (Chemical Engineering Journal, 2023)

Dopamine induced multiple bonding in hyaluronic acid network to construct particle-free conductive hydrogel for reliable electro-biosensing - Ming-Ze Zeng; Dan Wei; Jie Ding; Yuan Tian; Xiao-Yang Wu; Zhi-Hong Chen; Cheng-Heng Wu; Jing Sun; Hua-Bing Yin; Hong-Song Fan (Carbohydrate Polymers, 2023)

Direct cytosolic delivery of DNA by creating fast closable holes in the cell membrane - Haili Wang; Wei You; Fan Gao; Lei Zhang; Aizong Shen; Fei Wang; Guang Chen; Xuan Nie; Lei Xia; Wei-Qiang Huang; Wen-Jian Zhang; Long-Hai Wang; et al. (Chemical Engineering Journal, 2023)

Cation-doped V2O5 microsphere as a bidirectional catalyst to activate sulfur redox reactions for lithium-sulfur batteries - Fan-Jun Liu; Wen-Lin Luo; Ze Zhang; Ji Yu; Jian-Xin Cai; Zhen-Yu Yang (Chemical Engineering Journal, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

Hydrogeological Control on Coalbed Methane Geochemistry in CO2/N2-Enriched Secondary Microbial Gas Areas: A Case Study in the Eastern Section of the Southern Junggar Basin, NW China - Baoxin Zhang; Ze Deng; Xuehai Fu; Yibing Wang; Longjiang Fan; Junqiang Kang; Zhenzhi Wang; Yanyan Ge (Natural Resources Research, 2022)

Effects of dietary glutathione on the growth performance, skin mucus antioxidant capacity, and immune responses of juvenile taimen Hucho taimen - Chang’an Wang; Shaoxia Lu; Ze Fan; Shicheng Han; Yang Liu; Haibo Jiang; Hongbai Liu (Aquaculture International, 2022)

Immobilization of Cd2+ and Pb2+ by biomineralization of the carbonate mineralized bacterial consortium JZ1 - Peng Zhang; Xiao-Qiang Liu; Li-yuan Yang; Hua-ze-yu Sheng; An-qi Qian; Ting Fan (Environmental Science and Pollution Research, 2022)

Evaluation of four novel protein sources as alternatives to soybean meal for two specifications of cage-farmed grass carp (Ctenopharyngodon idellus) deeds: Effect on growth performance, flesh quality, and expressions of muscle-related genes - Ze Fan; Chenhui Li; Di Wu; Jinnan Li; Liansheng Wang; Dingchen Cao; Linghong Miao; Shouqi Xie (Frontiers in Marine Science, 2022)
Costs associated with the use of soybean as a food source in aquaculture have imposed constraints on its use in this industry. Thus, research is now focusing on alternative sources of protein for use in aquaculture. Here, we assessed the effect of total replacement of soybean meal (SBM) by Clostridium autoethanogenum protein (CAP), Tenebrio molitor meal (TMM), cottonseed protein concentrate (CPC), and chlorella powder (CHP) in diets for small specimens (initial body weight: 239.72 ± 10.75 g) and large specimens (initial body weight: 638.32 ± 12.64 g) of grass carp. For that purpose, five isonitrogenous (300 g/kg) and isoaliphatic (58 g/kg) diets were formulated with SBM, CAP, TMM, CPC, and CHP as the only dietary protein source. Triplicate groups of fish were fed the experimental diets for 56 days. Results showed that irrespective of protein sources, large specimens of grass carp obtained the significantly reduced weight gain rate (WGR), specific growth rate, moisture, crude ash contents, drip loss rate, and gene expressions of muscle S6K, MyoD, and Myf-5, and the significantly increased crude protein and crude lipid contents, hardness, cohesiveness, adhesiveness, springiness, chewiness and shear force of muscles, and gene expressions of muscle TOR, 4EBP1, MyoG, MRF4, and MSTN-1. Regardless of size, the CHP group possessed markedly higher WGR, protein efficiency ratio, crude protein contents, hardness, adhesiveness, chewiness values, and gene expression levels of muscle TOR, 4EBP1, Myf-5, and MRF4, and significantly lower feed conversion rate, drip loss rate, and gene expressions of muscle S6K and MSTN-1. For small specimens or for large specimens, the essential amino acid contents of the CHP group were highest, and CHP markedly elevated the delicious amino acid and glycine contents in comparison with the SBM. Moreover, the CPC group also realized the function of promoting the growth and improving the flesh quality to a certain degree. However, total replacement of soybean meal by CAP and TMM in grass carp diets restrained the growth and damaged the flesh quality in varying degrees. Overall, comparatively, total replacement of SBM with CHP not only improved growth performance and feed use, but also enhanced the flavor and texture of the fish by improving the amino acid composition and water-holding capacity of muscle, as well as improving muscle growth by positively impacting the expression of genes associated with the regulation of growth and development. Therefore, CHP could be a potential protein source to replace SBM in diets for use in the aquaculture of grass carp.

PLXDC2 enhances invadopodium formation to promote invasion and metastasis of gastric cancer cells via interacting with PTP1B - Bin Wu; Yan-xia Wang; Jun-jie Wang; Dong-fang Xiang; Meng-si Zhang; Ze-xuan Yan; Wen-ying Wang; Jing-ya Miao; Xi Lan; Jia-jia Liu; Zheng-yan Li; Chuan Li; et al. (Clinical & Experimental Metastasis, 2022)
Plexin-domain containing 2 (PLXDC2) has been reported as an oncoprotein in several human malignancies. However, its expression and roles in gastric cancer remain largely unclear. In this study, we found that PLXDC2 was highly expressed in gastric cancer tissues, and the expression levels were positively correlated with clinicopathological features, but negatively with the patients’ outcome. Cox regression analysis identified PLXDC2 as an independent prognostic indicator for the patients. Knockdown of PLXDC2 markedly suppressed the in vitro invasion and in vivo metastasis of gastric cancer cells, while overexpression of PLXDC2 resulted in opposite effects. Mechanistically, PLXDC2 enhanced the level of phosphorylated Cortactin (p-Cortactin) by physically interacting with protein tyrosine phosphatase 1B (PTP1B), an important dephosphorylase, to prevent its dephosphorylating of p-Cortactin, thereby promoting the formation of invadopodia. Collectively, our results indicate that PLXDC2 contributes to the invasion and metastasis of gastric cancer by inhibiting PTP1B to facilitate the invadopodium formation, and may serve as a potential prognostic biomarker and a therapeutic target for this disease.

Shoot organogenesis and somatic embryogenesis in leaf tissue of Pulsatilla tongkangensis Y.N. Lee & T.C. Lee - Xiao-mei Zhao; Yu-ji Lian; Ze-lin Jin; Xue-jie Zhang; Yan Y; Shou-jin Fan (Plant Biotechnology Reports, 2022)

Sevoflurane-Induced Neurotoxicity in the Developing Hippocampus via HIPK2/AKT/mTOR Signaling - Lirong Liang; Ze Fan; Danyi He; Youyi Zhao; Tian Zeng; Bing Liu; Tianyuan Ma; Junjun Kang; Hui Zhang (Neurotoxicity Research, 2022)

Temporal Trend of Polycyclic Aromatic Hydrocarbons in Atmosphere: A Case Study within 24 h after Snowfall - Hui-Ze Fan; Fu-Jie Zhu; Wan-Li Ma (Bulletin of Environmental Contamination and Toxicology, 2022)

Lethal and sublethal effects of emamectin benzoate on life-table and physiological parameters of citrus red mite, Panonychus citri - Muhammad Musa Khan; Muhammad Waqar Ali; Muhammad Hafeez; Ze-Yun Fan; Shaukat Ali; Bao-Li Qiu (Experimental and Applied Acarology, 2021)

Investigation on the statistical characteristics of geoelectric field seismic anomalies in the North–South seismic belt of Chinese mainland - Hou Ze-Yu; An Zhang-Hui; Fan Ying-Ying; Tan Da-Cheng; Fu A-Long; Wei Lei (Acta Geophysica, 2021)

Non-consumptive effects of Encarsia formosa on the reproduction and metabolism of the whitefly Bemisia tabaci - Ze-Yun Fan; Zhan-Peng Zhu; Jing Peng; Xin-Yi Chen; Zi-Tong Lu; Hui-Peng Pan; Bao-Li Qiu (BioControl, 2021)

Dietary magnesium requirement on dietary minerals and physiological function of juvenile hybrid sturgeon (Acipenser schrenckii♀ × Acipenser baerii♂) - Yuanyuan Zhang; Ze Fan; Di Wu; Jinnan Li; Qiyou Xu; Hongbai Liu; Liansheng Wang (Aquaculture International, 2021)
Sturgeons are an economically important freshwater aquacultural fish in China and elsewhere. Research was conducted to study the magnesium requirement of juvenile hybrid sturgeon ( Acipenser schrenckii ♀ × Acipenser baerii ♂) based on mineral composition, proximate chemical analysis, antioxidant enzyme levels, and growth metrics. Different levels of magnesium supplements (43.2, 157.3, 326.5, 549.6, 743.9, 938.4, and 1118.2 mg kg −1 ) were fed to juvenile sturgeon for 8 weeks. Five hundred twenty-five juvenile hybrid sturgeons (an average initial body weight of 7.65 g) were randomly divided into 7 groups with 3 replicates each (25 fish per replicate, tanks of 100×50×50 cm, dissolved oxygen ≥ 5.0 mg L −1 , 12 light:12 dark) and fed 4 times per day with the experimental diets containing 40.78% crude protein and 10.03% crude fat. The body tissues and blood of fish were then sampled and analyzed. Growth performance was not significantly different between treatments ( P> 0.05). The optimal dietary magnesium requirement for hybrid sturgeon was estimated to be 355.16, 573.6, or 584.6 mg kg −1 dietary magnesium based on whole-body Mg retention, the whole-body or vertebrae magnesium content versus dietary magnesium levels. The whole-body calcium to phosphorus ratio of the 43.2 and 326.5 mg kg −1 groups was significantly higher than that of the 938.4 mg kg −1 group ( P −1 improved the antioxidant capacity by decreasing the serum malondialdehyde and enhancing serum superoxide dismutase, glutathione peroxidase, and catalase activities.

Monsoon precipitation variations in Myanmar since AD 1770: linkage to tropical ocean‐atmospheric circulations - Zaw Zaw; Ze-Xin Fan; Achim Bräuning; Wenjie Liu; Narayan Prasad Gaire; Kay Zin Than; Shankar Panthi (Climate Dynamics, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Combining targeted sequencing and ultra-low-pass whole-genome sequencing for accurate somatic copy number alteration detection - Junfeng Fu; Weihua Guo; Cheng Yan; Zhenyang Lv; Yu Wang; Ze Wang; Zhe Fan; Ting Lei (Functional & Integrative Genomics, 2021)

Inversion analysis of the shear strength parameters for a high loess slope in the limit state - Xiao-yan Lin; Lin-fan Zhang; Ze Yang; Ping Li; Tong-lu Li (Journal of Mountain Science, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

High-precision downward continuation of potential fields algorithm utilizing adaptive damping coefficient of generalized minimal residuals - Zhi-Hou Zhang; Xiao-Long Liao; Ze-Yu Shi; Anthony R. Lowry; Yu Yao; Run-Qi Lu; Xiang-Tai Fan; Peng-Fei Liu; Si-Wei Zhao (Applied Geophysics, 2020)

Long‐term physiological and growth responses of Himalayan fir to environmental change are mediated by mean climate - Shankar Panthi; Ze‐Xin Fan; Peter van der Sleen; Pieter A. Zuidema (Global Change Biology, 2020)
High‐elevation forests are experiencing high rates of warming, in combination with CO 2 rise and (sometimes) drying trends. In these montane systems, the effects of environmental changes on tree growth are also modified by elevation itself, thus complicating our ability to predict effects of future climate change. Tree‐ring analysis along an elevation gradient allows quantifying effects of gradual and annual environmental changes. Here, we study long‐term physiological (ratio of internal to ambient CO 2 , i.e., C i /C a and intrinsic water‐use efficiency, iWUE) and growth responses (tree‐ring width) of Himalayan fir ( Abies spectabilis ) trees in response to warming, drying, and CO 2 rise. Our study was conducted along elevational gradients in a dry and a wet region in the central Himalaya. We combined dendrochronology and stable carbon isotopes (δ 13 C) to quantify long‐term trends in C i /C a ratio and iWUE (δ 13 C‐derived), growth (mixed‐effects models), and evaluate climate sensitivity (correlations). We found that iWUE increased over time at all elevations, with stronger increase in the dry region. Climate–growth relations showed growth‐limiting effects of spring moisture (dry region) and summer temperature (wet region), and negative effects of temperature (dry region). We found negative growth trends at lower elevations (dry and wet regions), suggesting that continental‐scale warming and regional drying reduced tree growth. This interpretation is supported by δ 13 C‐derived long‐term physiological responses, which are consistent with responses to reduced moisture and increased vapor pressure deficit. At high elevations (wet region), we found positive growth trends, suggesting that warming has favored tree growth in regions where temperature most strongly limits growth. At lower elevations (dry and wet regions), the positive effects of CO 2 rise did not mitigate the negative effects of warming and drying on tree growth. Our results raise concerns on the productivity of Himalayan fir forests at low and middle (

Physiological response of Secale cereale L. seedlings under freezing-thawing and alkaline salt stress - Ze Gong; Weiwei Chen; Guozhang Bao; Jiaxing Sun; Xuemei Ding; Cunxin Fan (Environmental Science and Pollution Research, 2020)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Two new phenylspirodrimanes from the deep-sea derived fungus Stachybotrys sp. MCCC 3A00409 - Xin-hua Ma; Wei-min Zheng; Kai-hui Sun; Xiao-fan Gu; Xian-ming Zeng; Hai-tao Zhang; Tian-hua Zhong; Zong-ze Shao; Yong-hong Zhang (Natural Product Research, 2019)

Complete plastid genome of Bupleurum boissieuanum, an endemic herb plant in western China - Ying Wu; Tian-Ze Zhang; Dai-Yu Qiu; Qiang Chai; Wei-Bing Fan; Zhong-Hu Li; Min-Feng Fang (Conservation Genetics Resources, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

CYP46A1 and the APOEε4 Allele Polymorphisms Correlate with the Risk of Alzheimer’s Disease - Ling Li; Fan Zeng; Yu-Hui Liu; Hui-Yun Li; Shu-Yang Dong; Ze-Yan Peng; Yan-Jiang Wang; Hua-Dong Zhou (Molecular Neurobiology, 2018)

Target enrichment sequencing in cultivated peanut (Arachis hypogaea L.) using probes designed from transcript sequences - Ze Peng; Wen Fan; Liping Wang; Dev Paudel; Dante Leventini; Barry L. Tillman; Jianping Wang (Molecular Genetics and Genomics, 2017)

Characterization of Antimicrobial Peptides Isolated from the Processing by-Products of African Catfish Clarias gariepinus - Tao Li; Xiaomei Wang; Yan Wang; Tianguo Fan; Yunxia Xu; Ze Fan (International Journal of Peptide Research and Therapeutics, 2017)

Warming induced growth decline of Himalayan birch at its lower range edge in a semi-arid region of Trans-Himalaya, central Nepal - Achyut Tiwari; Ze-Xin Fan; Alistair S. Jump; Zhe-Kun Zhou (Plant Ecology, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Early detection of white mold caused by Sclerotinia sclerotiorum in potato fields using real-time PCR - Mohammad Reza Ojaghian; Jing-Ze Zhang; Fan Zhang; Wen Qiu; Xiao-Lin Li; Guan-Lin Xie; Shui-Jin Zhu (Mycological Progress, 2016)

Strategy to Suppress Oxidative Damage-Induced Neurotoxicity in PC12 Cells by Curcumin: the Role of ROS-Mediated DNA Damage and the MAPK and AKT Pathways - Xiao-yan Fu; Ming-feng Yang; Ming-zhi Cao; Da-wei Li; Xiao-yi Yang; Jing-yi Sun; Zong-yong Zhang; Lei-lei Mao; Shuai Zhang; Feng-ze Wang; Feng Zhang; Cun-dong Fan; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

The role of HMGB1-RAGE axis in migration and invasion of hepatocellular carcinoma cell lines - Ruo-Chan Chen; Pan-Pan Yi; Rong-Rong Zhou; Mei-Fang Xiao; Ze-Bing Huang; Dao-Lin Tang; Yan Huang; Xue-Gong Fan (Molecular and Cellular Biochemistry, 2014)

Climate change trend in China, with improved accuracy - Tian-Xiang Yue; Na Zhao; R. Douglas Ramsey; Chen-Liang Wang; Ze-Meng Fan; Chuan-Fa Chen; Yi-Min Lu; Bai-Lian Li (Climatic Change, 2013)

Phylogeography of Sophora davidii (Leguminosae) across the ‘Tanaka‐Kaiyong Line’, an important phytogeographic boundary in Southwest China - Deng Mei Fan; Ji Pei Yue; Ze Long Nie; Zhi Min Li; Hans Peter Comes; Hang Sun (Molecular Ecology, 2013)
The ‘Tanaka‐Kaiyong Line’ ( TKL ) is a major phytogeographic boundary in Southwest China, separating East Asia's Sino‐Himalayan and Sino‐Japanese Floras. However, little is known about the importance of this boundary in promoting intraspecific phylogeographic subdivision and divergence. Using chloroplast (cp DNA ) and nuclear‐intron ( nDNA ) sequence data, we reconstructed the population history of Sophora davidii , a drought‐tolerant riparian shrub widely distributed on either side of the TKL . Specifically, we aimed at testing two long‐standing explanations for possible vicariant events across the TKL: (i) Late Pliocene ( c . 3 Ma) geological uplift of the eastern Qinghai‐Tibetan Plateau (QTP) or (ii) a sharp environmental gradient associated with the establishment of different monsoon regimes on either side of the TKL during the (Late) Pleistocene. Our genealogical analyses detected a major west–east split in cpDNA, geographically largely consistent with the TKL, and dated to c . 1.28 Ma (95% HPD: 0.21–2.96 Ma), hence postdating the latest phase of eastern QTP uplift. Furthermore, integrating cpDNA phylogeographic patterns with mismatch analyses, we found multiple refugial isolation and long‐term demographic stability of populations in the west (Hengduan Mountain Range) compared with extensive range expansions in the east, possibly during the last glacial period(s) and followed by differentiation into regional sublineages (southeast: Yunnan‐Guizhou Plateau vs. northeast: Qinling Mts./Loess Plateau). Although nuclear differentiation was less marked, the geographical pattern of nDNA haplotypes provided some further indication of the species' eastward expansion, possibly from source populations located just east of the TKL (lower Jinshajiang region). Overall, the present data reject the geological (tectonic) explanation for the TKL and, instead, provide supportive evidence for its role as a climatically driven barrier to present‐day plant dispersal. In addition, our study highlights changing temperatures and vegetation types during the last glacial period(s), along with aspects of regional topography, to be important determinants of the glacial eastward expansion of S. davidii . In consequence, our study lends support to a ‘glacial out‐of‐Hengduan Mts’. hypothesis for the xerophytic‐riparian flora of Southwest China, which in turn is inconsistent with the traditional view of the TKL as a ‘classical’ vicariant‐biogeographic boundary.

Potential hydraulic efficiency in angiosperm trees increases with growth‐site temperature but has no trade‐off with mechanical strength - Shi‐Bao Zhang; Kun‐Fang Cao; Ze‐Xin Fan; Jiao‐Lin Zhang (Global Ecology and Biogeography, 2013)
Aim Xylem structures are closely related to a tree's hydraulic efficiency and mechanical stability, both of which affect the life history and ecological strategy of a species. Although mechanical strength and hydraulic capacity can be shaped by the environment, no such associations between hydraulic efficiency and climatic variables have been reported across a wide range of tree species. Location Y unnan, south‐west C hina. Methods We compiled a data set for vessel density, vessel diameter ( D ), potential hydraulic conductivity ( K p ), wood density ( WD ), modulus of rupture ( MOR ) and modulus of elasticity ( MOE ) from 316 angiosperm tree species. Our objective was to examine the correlations among xylem traits and climatic variables. We hypothesized that both hydraulic efficiency and mechanical strength would vary along climatic gradients, but that a trade‐off would occur between them. Results All xylem traits varied significantly across species, but the magnitudes of variation were greater for vessel traits than for mechanical properties. Values for K p and D increased with mean annual temperature ( MAT ) in both evergreen and deciduous trees, but they were significantly correlated with aridity index ( AI ) in evergreen species only. Both WD and MOR were significantly correlated with MAT only in evergreen trees. MOR decreased with increasing AI in the evergreens, but not in deciduous trees. These findings indicated that xylem development in evergreens is more sensitive to environmental changes than in deciduous trees. However, stem hydraulic traits are independent of mechanical properties. Main conclusions Consistent with our hypothesis, both hydraulic efficiency and mechanical strength of angiosperm trees are influenced by the environment, with temperature having a more important effect on hydraulic efficiency than precipitation. However, no trade‐off exists between efficiency and strength. This absence of a link is explained because angiosperms have xylem tissue that specifically functions in either mechanical strength or water transport.

Spatiotemporal variability of reference evapotranspiration and its contributing climatic factors in Yunnan Province, SW China, 1961–2004 - Ze-Xin Fan; Axel Thomas (Climatic Change, 2013)

Novel and ancient HMW glutenin genes from Aegilops tauschii and their phylogenetic positions - Wen-Jie Chen; Xing Fan; Bo Zhang; Bao-Long Liu; Ze-Hong Yan; Lian-Quan Zhang; Zhong-Wei Yuan; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Phosphorylation of GIT1 tyrosine 321 is required for association with FAK at focal adhesions and for PDGF-activated migration of osteoblasts - Yongxin Ren; Lipeng Yu; Jin Fan; Ze Rui; Zhengzhe Hua; Zitao Zhang; Ning Zhang; Guoyong Yin (Molecular and Cellular Biochemistry, 2012)

Novel HMW glutenin genes from Aegilops tauschii and their unique structures - Wen-Jie Chen; Zhong-Wei Yuan; Lian-Quan Zhang; Xing Fan; Ze-Hong Yan; Ji-Rui Wang; You-Liang Zheng; Huai-Gang Zhang; Deng-Cai Liu (Genes & Genomics, 2012)

A robust estimator for the accuracy assessment of remote-sensing-derived DEMs - Chuan-Fa Chen; Ze-Meng Fan; Tian-Xiang Yue; Hong-Lei Dai (International Journal of Remote Sensing, 2012)

Spatial and temporal temperature trends on the Yunnan Plateau (Southwest China) during 1961–2004 - Ze‐Xin Fan; Achim Bräuning; Axel Thomas; Jin‐Bao Li; Kun‐Fang Cao (International Journal of Climatology, 2011)
Monthly mean (TEM), maximum ( T max ) and minimum ( T min ) surface air temperatures at 119 meteorological stations on the Yunnan Plateau (YP, Southwest China) were analysed for temporal trends and spatial variation patterns during the period 1961–2004. Linear trend analyses revealed that annual temperature over the YP increased at a rate of 0.3 °C/decade during the period 1961–2004, while warming trend of 0.33 °C/decade and 0.26 °C/decade was observed for winter and summer temperatures, respectively. Warming trends of nighttime minimum temperature are more pronounced than those of daytime maximum temperature, especially during winter season. Consequently, a decreasing trend of diurnal temperature ranges (DTR = T max − T min ) was observed. Five spatial patterns of temperature variability were objectively defined by rotated empirical orthogonal function (EOF) analysis, which are associated with distinct temporal temperature variations and geographical area over the YP. Annual temperature increases were found to be most pronounced in the southern and northwestern (high‐elevation) parts of the YP, whereas the hot‐dry valleys along the Yangtze and Red River basins experienced cooling during the past four decades. Copyright © 2010 Royal Meteorological Society

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Induction of the activities of antioxidative enzymes and the levels of malondialdehyde in cucumber seedlings as a consequence of Bemisia tabaci (Hemiptera: Aleyrodidae) infestation - Shi-Ze Zhang; Bao-Zhen Hua; Fan Zhang (Arthropod-Plant Interactions, 2008)

Tree‐ring based drought reconstruction in the central Hengduan Mountains region (China) since A.D. 1655 - Ze‐Xin Fan; Achim Bräuning; Kun‐Fang Cao (International Journal of Climatology, 2008)
We developed four tree ring‐width chronologies of three species ( Picea likiangensis Pritz, Tsuga dumosa (D. Don) Eichler and Abies ernestii Rehd.) in the central Hengduan Mountains, north‐western Yunnan, China. Although the four chronologies come from different species, significant correlations exist among the chronologies (mean r = 0.47), and the first principal component accounts for 60.5% of total variance over their common period 1655–2005. Correlation and response function analyses showed that pre‐monsoon (March, April) precipitation and relative humidity and Palmer drought severity index (PDSI) have positive effects on radial growth, while temperature in March influences tree growth negatively. This indicates that tree growth is generally limited by spring‐moisture availability. The spring (March–May) drought reconstruction was verified with independent data, and accounts for 42% of the actual PDSI variance during their common period 1951–2000. Wet springs occurred during AD 1690s, 1715–1730, 1750s, 1780s, 1825–1850, 1900s, 1930–1960, and 1990–present. Dry springs occurred during AD 1700–1715, 1733–1745, 1790–1820, 1860–1890, 1910–1925, and 1960–1990. Copyright © 2008 Royal Meteorological Society

Up-regulation of IL-1 receptor type I and tyrosine hydroxylase in the rat carotid body following intraperitoneal injection of IL-1β - Xi-Jing Zhang; Xi Wang; Li-Ze Xiong; Juan Fan; Xiao-Li Duan; Bai-Ren Wang (Histochemistry and Cell Biology, 2007)

Y chromosomes of prehistoric people along the Yangtze River - Hui Li; Ying Huang; Laura F. Mustavich; Fan Zhang; Jing-Ze Tan; Ling-E Wang; Ji Qian; Meng-He Gao; Li Jin (Human Genetics, 2007)